Macromol. Chem. Phys. 18/2017. Issue 18 (September 2017) - Han, Lu; Zhang, Kan; Ishida, Hatsuo; Froimowicz, Pablo
Abstract : Front Cover : Science and technology of thermosets is constantly increasing its areas of researches, interests, and applications. Polybenzoxazines in particular are the youngest in the field and are already hoarding up the center of attention in every subject. This is briefly represented in the cover by showing the key role of benzoxazine resins, the building block of polybenzoxazines, highlighted at the central position of the typical and general science and technology tetrahedron. This is reported by Lu Han, Kan Zhang, Hatsuo Ishida, * and Pablo Froimowicz* in article number1600562 .